INNOVATIONS IN MICRO/NANO PATTERNING USING TOOL-BASED METHODS - Rahman, Mustafizur (IIUM Engineering Journal, 2016)
In recent years, the trend in miniaturization of products has been pervasive in areas such as information technology, biotechnology, and the environmental and medical industries. Micro/Nano patterning is the key supporting technology that has to be developed to meet the challenges posed by the requirements of product miniaturization and the industrial realization of nanotechnology. Micro/Nano patterning techniques can be carried out by techniquesbased on energy beams or solid cuttingtools (tool-based micro-machining). Tool-based micro/nano patterning is a relatively new area; however, over the lasttwo decades, owing to the predominant trend in miniaturization of products, Micro/Nano patterning using tool-based techniques has become a key supportive technology. The energybeam-based patterning process (electron-beam lithography) hassome limitations due to poor control of 3D structures, low material removal rate and low aspect ratio. Moreover, these processes requirespecial facilities, and the maximum achievable thickness is relatively small. Some of theselimitations can be overcome by a tool-based approach using ultra-precision machine tools and solid tools as cutting elements to produce the micro-features with well-controlled shape and tolerances. These Micro/Nano machining-based patterning techniques have been achieved through a paradigm shift in the ideas and processes of conventional machining. In this paper, an attempt has beenmade to present the recent innovations in tool-based micro/nano patterning processes.